ANALISIS TINGKAT KUALITAS KINERJA WEBSITE SMA NEGERI 60 JAKARTA MENGGUNAKAN FRAMEWORK WEBQUAL 4.0 DAN IPA - Moh Teddy Reza (2023)
The rapid development of information technology nowadays has transformed almost every aspect of life, including education. SMA Negeri 60 Jakarta, as one of many high schools in Jakarta, utilizes a website as a supporting tool for information source and learning. However, there has been no assessment conducted on the quality of the school's website, despite its usage since 2018. Therefore, this research uses the WebQual 4.0 framework and Importance Performance Analysis method to measure the website's performance quality. Through data collection using a Google Form questionnaire from 346 respondents, variations in the indicators of suitability level and gap values were identified. The analysis results reveal indicators with the lowest (72%) and highest (101%) suitability levels, while the gap values range from the largest (-1.243) to the smallest (0.026). In the Quadrant Analysis, 9 indicators are identified for low/high-priority improvement. Based on these findings, it is recommended to focus on improving the indicators located in Quadrants 1 and 3, while no recommendations are given for Quadrants 2 and 4 as they are considered to meet user expectations. These recommendations are provided in the form of descriptive explanations and application designs, which were evaluated and provided feedback by 3 experts in website programming. The feedback indicated that the given recommendations were sufficient.